Teach reading creatively reading and writing as communication - May, Frank B.; Fulton, Louise; May, Frank B. (Upper Saddle River, N.J. Pearson/Merrill/Prentice Hall, 2006)
Formerly published as "Reading and Writing as Communication", this book aims to provide new teachers with proven reading strategies through an integrated narrative.
Rev. ed. of: Reading as communication / Frank B. May, Louis Rizzardi. 6th ed. c2002.
Keywords: Reading; Literacy